NILAI - NILAI PENDIDIKAN KARAKTER DALAM IBADAH PUASA (KAJIAN Q.S AL-BAQARAH AYAT 183) - Wibowo, Ginanjar; Mukromin, Mukromin; Fuadi, Salis Irvan (FAKULTAS ILMU TARBIYAH DAN KEGURUAN UNIVERSITAS SAINS AL-QUR'AN, 2022)
This writing, entitled Values ​​of Character Education in Fasting Worship (Study of Q. S Al-Baqarah Verse 183) aims to determine the content of Q.S Al-Baqarah verse 183, to determine the values ​​of character education in fasting, and to determine the relationship between character education contained in Islamic religious education Q.S Al-Baqarah verse 183. The type of research used is qualitative research where the type of research is liberary research. The data analysis technique uses content analysis while for the interpretation of the Qur'an using the tahlili method. Based on the results of this study, it can be concluded that there are character education values ​​that can be trained in the fasting worship of Ramadan so that it can be used as physical and spiritual training. Such as practicing honesty, practicing patience, practicing discipline, practicing gratitude, practicing an independent attitude, and being able to create a sense of social care for fellow human beings. After carrying out the full fasting month of Ramadan, you must continue to cultivate morals, ethics or morals optimally so that honesty, patience, discipline, gratitude, independence, and social care can be applied in everyday life.